Supercapattery performances of nanostructured cerium oxide synthesized using polymer soft-template. (April 2020) - Junais, Pulikkathumbayil Muhammed; Athika, Mattath; Govindaraj, Gurusamy; Elumalai, Perumal
Highlights: Nanostructured ceria is prepared by using polymer soft-template. CeO2 electrode exhibits a specific capacity of 400 C g −1 at 1 A g −1 . Presence of Ce 3+ in CeO2 enhances the electrical conductivity and electrochemical performances. Fabricated supercapattery using CeO2 positive electrode and rGO negative electrode shows specific energy of 20 W h kg −1 at a specific power of 1475 W kg −1 . Supercapattery shows capacity retention of even 82% after 10, 000 cycling. Abstract: In the present study, we demonstrate the supercapattery performances of cerium oxide (CeO2 ) nanoparticles prepared using polyvinyl alcohol (PVA)/ Polyvinylpyrrolidone (PVP) soft template method. The formation of the CeO2 nanoparticle was confirmed using X-ray diffraction, Raman and UV-visible spectroscopic analyses. The surface morphology was confirmed using a scanning electron microscope. High-resolution transmission electron microscope coupled with energy dispersive X-ray analysis of the CeO2 nanoparticle revealed the presence of spherical nano-grains in the size range of 8–12 nm. The electrochemical properties of the CeO2 electrode revealed good reversibility with high specific capacity of 400 C g −1 at 1 A g −1 in 1 M KOH. Laboratory proto-type supercapattery was fabricated using CeO2 as positive electrode and reduced graphene-oxide (rGO) as negative electrode that delivered specific energy of 20 Wh kg −1 and high specific power of 1475 W kg −1 in the optimum potential window of 0–1 V. The excellent performance of CeO2 supercapattery was attributed to the presence of high concentration of surface Ce 3+ ions in the CeO2 and large surface area. The practical viability of the fabricated supercapattery was demonstrated by powering a commercial 2.8 V light-emitting diode (LED) for more than 10 min on a single charge. Graphical abstract: Image, graphical abstract